JMATH Journal of Mathematics 2314-4785 2314-4629 Hindawi Publishing Corporation 409329 10.1155/2013/409329 409329 Research Article Asymptotic Behavior of Ground State Radial Solutions for p-Laplacian Problems Ben Othman Sonia 1 Chemmam Rym 1 Mâagli Habib 2 Gallego Francisco B. 1 Département de Mathématiques Faculté des Sciences de Tunis Campus Universitaire 2092 Tunis Tunisia 2 King Abdulaziz University College of Sciences and Arts Rabigh Campus Department of Mathematics. P.O. Box 344 Rabigh 21911 Saudi Arabia kau.edu.sa 2013 3 02 2013 2013 13 09 2012 28 12 2012 2013 Copyright © 2013 Sonia Ben Othman et al. This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Let p>1, we take up the existence, the uniqueness and the asymptotic behavior of a positive continuous solution to the following nonlinear problem in (0,+), (1/A)(Aϕp(u))+q(x)uα=0, limx0Aϕp(u)(x)=0, limx+u(x)=0, where α<p1,   ϕp(t)=t|t|p2   (t), A is a positive differentiable function in (0,+) and q is a positive continuous function in (0,+) such that there exists c>0 satisfying for each x in (0,+), 1/cq(x)(1+x)βexp(1x+1(z(s)/s)ds)c, βp and zC([1,+)) such that limt+z(t)=0.

1. Introduction

Let p>1 and α<p-1. The following differential equation: (1)Lpu:=1A(AΦp(u))=-q(x)uα,in  (0,ω),ω(0,+] has been studied with various boundary conditions, where A is a continuous function in [0,+), differentiable and positive in (0,+), q is a nonnegative continuous function in (0,+), and Φp(t)=t|t|p-2, (t) (see ).

For a function u depending only on t=|x|, xn, and A(t)=tn-1, the operator Lp is the radially symmetric p-Laplacian Δpu=div(|u|p-2u) in n and the equation of type (1) arises also as radial solutions of the Monge-Ampère equation (see ).

In this paper, our main purpose is to obtain the existence of a unique positive solution to the following boundary value problem: (P)1A(AΦp(u))+q(x)uα=0,in(0,),AΦp(u)(0):=limx0+AΦp(u)(x)=0,limx+u(x)=0, and to establish estimates on such solution under an appropriate condition on q.

The study of this type of (1) is motivated by [5, 15]. Namely, in the special case A(t)=tn-1g(t), gC1(+) and f(u)=uα, α>-1, the authors in  studied (1) and gave some uniqueness results. In this work, we consider a wider class of weights A and we aim to extend the study of (1) in , to α<p-1.

For the case α<0, the problem (P) has been studied in . Indeed, the authors of  proved the following existence result.

Theorem 1.

The problem (P) has a unique positive solution uC([0,+)) satisfying for each x(0,+)(2)1cGpq(x)u(x)c(Gpq(x))(p-1)/(p-1-α), where c is a positive constant and Gpq is the function defined on (0,+) by (3)Gpq(x):=x+(1A(t)0tA(s)q(s)ds)1/(p-1)dt.

We shall improve in this paper the above asymptotic behavior of the solution of problem (P) and we extend the study of (P) to 0α<p-1.

The pure elliptic problem of type (Q)-Δu+q(x)uα=0,xn(n3),α<1,u>0  in  n,lim|x|+u(x)=0 has been investigated by several authors with zero Dirichlet boundary value; we refer the reader to  and the references therein. More recently, applying Karamata regular variation theory, Chemmam et al. gave in  the asymptotic behavior of solutions of problem (Q). In this work, we aim to extend the result established in  to the radial case associated to problem (P).

To simplify our statements, we need to fix some notations and make some assumptions. Throughout this paper, we shall use 𝒦, to denote the set of Karamata functions L defined on [1,+) by (4)L(t):=cexp(1tz(s)sds), where c is a positive constant and zC([1,[) such that limt+z(t)=0.

It is clear that L𝒦 if and only if L is a positive function in C1([1,[) such that (5)limttL(t)L(t)=0. For two nonnegative functions f and g on a set S, we write f(x)g(x), xS, if there exists a constant c>0 such that (1/c)g(x)f(x)cg(x), for each xS.

The letter c will denote a generic positive constant which may vary from line to line.

Furthermore, we point out that if f is a nonnegative continuous function in [0,+[, then the function Gpf defined on (0,+) by (6)Gpf(x):=x+(1A(t)0tA(s)f(s)ds)1/(p-1)dt is the solution of the problem (7)-1A(AΦp(u))=f,in(0,+),AΦp(u)(0)=0,limx+u(x)=0.

As it is mentioned above, our main purpose in this paper is to establish existence and global behavior of a positive solution of problem (P). Let us introduce our hypotheses.

Here, the function A is continuous in [0,+), differentiable and positive in (0,+) such that (8)A(x)xλ with λ>p-1.

The function q is required to satisfy the following hypothesis.

(H) q is a positive measurable function on (0,+) such that (9)q(x)L(1+x)(1+x)β, with βp and the function L𝒦 such that 1+t(1-β)/(p-1)(L(t))1/(p-1)dt<+.

Remark 2.

We need to verify condition (10)  1+t(1-β)/(p-1)(L(t))1/(p-1)dt<+ in hypothesis (H), only if β=p, (see Lemma 6 below).

As a typical example of function q satisfying (H), we quote the following.

Example 3.

Put q(x):=(1+x)-β(log(x+2))-ν,x(0,+). Then for β>p and ν or β=p and ν>p-1, the function q satisfies (H).

Now, we are ready to state our main result.

Theorem 4.

Assume (H). Then problem (P) has a unique positive continuous solution u satisfying for x(0,+), (11)u(x)θβ(x), where θβ is the function defined on [0,+) by (12)θβ(x):={(x+1(L(s))1/(p-1)sds)(p-1)/(p-1-α),if  β=p,(L(1+x))1/(p-1-α)(1+x)(β-p)/(p-1-α),if  p<β<(λ+1)(p-1-α)+αpp-1,(1+x)(p-1-λ)/(p-1),if  β>(λ+1)(p-1-α)+αpp-1,(1+x)(p-1-λ)/(p-1)(1x+2L(s)sds)1/(p-1-α),if  β=(λ+1)(p-1-α)+αpp-1.

The main body of the paper is organized as follows. In Section 2, we establish some estimates and we recall some known results on functions belonging to 𝒦. Theorem 4 is proved in Section 3. The last Section is reserved to some applications.

2. Key Estimates

In what follows, we are going to give estimates on the functions Gpq and Gp(qθβα), where q is a function satisfying (H) and θβ is the function given by (12). First, we recall some fundamental properties of functions belonging to the class 𝒦, taken from [17, 22].

Lemma 5.

Let L1,L2𝒦,m and ε>0. Then one has L1L2𝒦,L1m𝒦 and limt+t-εL1(t)=0.

Lemma 6 (Karamata’s theorem).

Let μ and L be a function in 𝒦. Then one has the following properties:

If μ<-1, then 1sμL(s)ds converges and (13)tsμL(s)ds~t-t1+μL(t)μ+1.

If μ>-1, then 1sμL(s)ds diverges and (14)1tsμL(s)ds~tt1+μL(t)μ+1.

Lemma 7.

Let L𝒦. Then there exists m>0 such that for t1 and c>0(15)1(1+c)mL(t)L(c+t)(1+c)mL(t).

Lemma 8.

Let L𝒦, then one has (16)t1t+1L(s)sds𝒦. If further 1(L(s)/s)ds converges, one has (17)ttL(s)sds𝒦.

Now, we are able to prove the following propositions which play a crucial role in this paper.

Proposition 9.

Let q be a function satisfying (H). Then one has for x(0,)(18)Gpq(x)Ψ(x), where ψ is the function defined by (19)Ψ(x):={x+1(L(s))1/(p-1)sds,if  β=p,(L(x+1))1/(p-1)(x+1)(β-p)/(p-1),if  p<β<λ+1,(x+1)(p-1-λ)/(p-1)(1x+2L(s)sds)1/(p-1),if  β=λ+1,(x+1)(p-1-λ)/(p-1),if  β>λ+1.

Proof.

For x(0,), we have (20)Gpq(x)xtλ/(1-p)(0tsλ(1+s)-βL(1+s)ds)1/(p-1)dt. Put (21)h(x)=:xtλ/(1-p)(0tsλ(1+s)-βL(1+s)ds)1/(p-1)dt,x(0,). To prove the result, it is sufficient to show that h(x)Ψ(x) for x(0,).

Since the function h is continuous and positive in [0,1], we have (22)h(x)1,x[0,1]. Now, assume that x[1,), then we have (23)h(x)=xtλ/(1-p)(01sλ(1+s)-βL(1+s)ds+1tsλ(1+s)-βL(1+s)ds)1/(p-1)dt. It follows from Lemma 7 that (24)h(x)xtλ/(1-p)(1+1tsλ-βL(s)ds)1/(p-1)dt. To reach our estimates, we consider the following cases.

(i) If p<β<λ+1, then it follows from Lemma 6 that (25)h(x)xt(1-β)/(p-1)L(t)1/(p-1)dt. Now, using Lemma 5 and again Lemma 6, we deduce that (26)h(x)(L(x))1/(p-1)x(β-p)/(p-1).

(ii) If β>λ+1, then it follows from Lemma 6, that 1sλ-βL(s)ds<. So, since λ>p-1, we have (27)h(x)x(p-λ-1)/(p-1).

(iii) If β=λ+1, then for each t[x,+), we have (28)(1+1tL(s)sds)1/(p-1)(1t+1L(s)sds)1/(p-1). Since the function t(1t+1(L(s)/s)ds)1/(p-1) is in 𝒦, then using the fact that λ>p-1 and Lemma 6, we obtain that (29)h(x)x(p-1-λ)/(p-1)(1x+1L(s)sds)1/(p-1).

(iv) If β=p, we have by Lemma 6 that (30)1tsλ-pL(s)dstλ-p+1L(t), this yields to (31)h(x)xL1/(p-1)(t)tdt. Hence, we reach the result by combining (22) with the estimates stated in each case above. This completes the proof.

Proposition 10.

Let q be a function satisfying (H) and let θβ be the function given by (12). Then for x(0,), one has (32)Gp(qθβα)(x)θβ(x).

Proof.

Let βp and λ>p-1, we obtain by simple calculus that for x(0,), (33)q(x)θβα(x)q~(x), where (34)q~(x)=:{L(1+x)(1+x)p(x+1(L(s))1/(p-1)sds)α(p-1)/(p-1-α),if  β=p,(L(1+x))(p-1)/(p-1-α)(1+x)(β-α(p-β)/(p-1-α)),if  p<β<(λ+1)(p-1-α)+αpp-1,L(1+x)(1+x)(β-α(p-1-λ)/(p-1)),if  β>(λ+1)(p-1-α)+αpp-1,L(1+x)(1+x)(1x+2L(s)sds)α/(p-1-α),if  β=(λ+1)(p-1-α)+αpp-1. So, one can see that (35)q~(x)=(1+x)-δL~(1+x), where δp. Then, using Lemmas 5, 7, and 8, we obtain that L~𝒦 and 1t(1-δ)/(p-1)(L~(t))1/(p-1)dt<+. Hence, it follows from Proposition 9 that (36)Gp(qθβα)(x)Gpq~(x)ψ~(x),x(0,), where ψ~ is the function defined in (19) by replacing L by L~ and β by δ. This ends the proof.

3. Proof of Theorem <xref ref-type="statement" rid="thm2">4</xref> 3.1. Existence and Asymptotic Behavior

Let q be a function satisfying (H) and let θβ be the function given by (12). By Proposition 10, there exists a constant m1 such that for each x(0,)(37)1mθβ(x)Gp(qθβα)(x)mθβ(x). We look now at the existence of positive solution of problem (P) satisfying (11).

For the case α<0, the existence of a positive continuous solution to problem (P) is due to . Now, we look to the existence result of problem (P) when 0α<p-1 and we give precise asymptotic behavior of such solution for α<p-1. For that, we split the proof into two cases.

Case 1 (<inline-formula><mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" id="M217"><mml:mi>α</mml:mi><mml:mo><</mml:mo><mml:mn mathvariant="normal">0</mml:mn></mml:math></inline-formula>).

Let u be a positive continuous solution of problem (P). So, in order to obtain estimates (11) on the function u, we need the following comparison result.

Lemma 11.

Let α<0 and u1,u2C1((0,))C([0,)) such that (38)-Lpu1(x)q(x)u1α,in(0,),AΦp(u1)(0)=0,  limx+u1(x)=0,(39)-Lpu2(x)q(x)u2α,in(0,),AΦp(u2)(0)=0,limx+u2(x)=0. Then u1u2.

Proof.

Suppose that u1(x0)>u2(x0) for some x0(0,). Then there exists x1,x2[0,], such that 0x1<x0<x2 and for x1<x<x2,u1(x)>u2(x) with u1(x2)=u2(x2),u1(x1)=u2(x1) or x1=0.

By an elementary argument, we have (40)AΦp(u2)(x1)AΦp(u1)(x1). On the other hand, since α<0, then u1α(x)<u2α(x), for each x(x1,x2). This yields to (41)Lpu1-Lpu2q(u2α-u1α)0,on  (x1,x2).

Using further (40), we deduce that the function ω(x):=(AΦp(u1)-AΦp(u2))(x) is nondecreasing on (x1,x2) with ω(x1)0. Hence, from the monotonicity of Φp, we obtain that the function x(u1-u2)(x) is nondecreasing on (x1,x2) with (u1-u2)(x1)0 and (u1-u2)(x2)=0. This yields to a contradiction, which completes the proof.

Now, we are ready to prove (11). Put c=m-α/(p-1-α) and v:=Gp(qθβα). It follows from (7) that the function v satisfies (42)-Lpv=qθβα,in(0,). According to (37), we obtain by simple calculation that (1/c)v and cv satisfy, respectively, (38) and (39). Thus, we deduce by Lemma 11 that (43)1cv(x)u(x)cv(x),x(0,). This implies (11) by using (37).

Case 2 (<inline-formula><mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" id="M252"><mml:mn mathvariant="normal">0</mml:mn><mml:mo>≤</mml:mo><mml:mi>α</mml:mi><mml:mo><</mml:mo><mml:mi>p</mml:mi><mml:mo>-</mml:mo><mml:mn mathvariant="normal">1</mml:mn></mml:math></inline-formula>).

Put c0=m(p-1)/(p-1-α) and let (44)Λ:={uC((0,));1c0θβuc0θβ}. Obviously, the function θβ belongs to C((0,)) and so Λ is not empty. We consider the integral operator T on Λ defined by (45)Tu(x):=Gp(quα)(x),x(0,). We shall prove that T has a fixed point in Λ, to construct a solution of problem (P). For this aim, we look at first that TΛΛ. Let uΛ, then we have for each x(0,)(46)1c0α(qθβα)(x)q(x)uα(x)c0α(qθβα)(x). This together with (37) implies that (47)1mc0α/(p-1)θβTumc0α/(p-1)θβ. Since mc0α/(p-1)=c0 and TΛC((0,)), then T leaves invariant the convex Λ. Moreover, since α0, then the operator T is nondecreasing on Λ. Now, let {uk}k be the sequence of functions in C([0,+)) defined by (48)u0=1c0θβ,uk+1=Tuk,fork. Since TΛΛ, we deduce from the monotonicity of T that for k, we have (49)u0u1ukuk+1c0θβ. Thanks to the monotone convergence theorem, we deduce that the sequence {uk}k converges to a function uΛ which satisfies (50)u(x)=Gp(quα)(x),x(0,). We conclude that u is a positive continuous solution of problem (P) satisfying (11).

3.2. Uniqueness

Assume that q satisfies (H). For α<0, the uniqueness of solution to problem (P) follows from Lemma 11. Thus in the following, we look at the case 0α<p-1. Let (51)Γ={uC((0,)):u(x)θβ(x)}. Let u and v be two positives solutions of problem (P) in Γ. Then there exists a constant k1 such that (52)1kvuk. This implies that the set (53)J={t(1,+),1tuvtu} is not empty. Now, put c:=infJ, then we aim to show that c=1.

Suppose that c>1, then we have (54)-Lpv+Lp(c-α/(p-1)u)=q(x)(vα-c-αuα),in(0,),limx0+(AΦp(v)-AΦp(c-α/(p-1)u))(x)=0,limx+(v-c-α/(p-1)u)(x)=0. So, we have -Lpv+Lp(c-α/(p-1)u)0 in (0,), which implies that the function (55)θ(x):=(AΦp(c-α/(p-1)u)-AΦp(v))(x) is nondecreasing on (0,+) with limx0+θ(x)=0. Hence from the monotonicity of Φp, we obtain that the function x(c-α/(p-1)u-v)(x) is nondecreasing on [0,+) with limx(c-α/(p-1)u-v)(x)=0. This implies that c-α/(p-1)uv. On the other hand, we deduce by symmetry that vcα/(p-1)u. Hence cα/(p-1)J. Now, since α<p-1 and c>1, we have cα/(p-1)<c. This yields to a contradiction with the fact that c:=infJ. Hence, c=1 and then u=v.

4. Applications 4.1. First Application

Let q be a positive measurable function in (0,) satisfying for x(0,)(56)q(x)(log(2+x))-σ(1+x)β, where the real numbers β and σ satisfy one of the following two conditions:

β>p and σ,

β=p and σ>p-1.

Using Theorem 4, we deduce that problem (P) has a positive continuous solution u in (0,) satisfying the following.

If β>((λ+1)(p-1-α)+αp)/(p-1), then for x(0,)(57)u(x)1(1+x)(λ-p+1)/(p-1).

If β=((λ+1)(p-1-α)+αp)/(p-1) and σ=1, then for x(0,)(58)u(x)1(1+x)(λ-p+1)/(p-1)(loglog(3+x))1/(p-1-α).

If β=((λ+1)(p-1-α)+αp)/(p-1) and σ<1, then for x(0,)(59)u(x)1(1+x)(λ-p+1)/(p-1)(log31+x)(1-σ)/(p-1-α).

If β=((μ+1)(p-1-α)+αp)/(p-1) and σ>1, then for x(0,)(60)u(x)1(1+x)(λ-p+1)/(p-1).

If p<β<((λ+1)(p-1-α)+αp)/(p-1), then for x(0,)(61)u(x)1(1+x)(β-p)/(p-1-α)(log(2+x))-σ/(p-1-α).

If β=p and σ>p-1, then for x(0,)(62)u(x)(log(2+x))(p-1-σ)/(p-1-α).

4.2. Second Application

Let q be a function satisfying (H) and let α,γ<p-1. We are interested in the following nonlinear problem: (63)-1A(AΦp(u))+γuΦp(u)u=q(x)uα,in(0,),AΦp(u)(0)=0,limxu(x)=0. Put v=u1-γ/(p-1), then by a simple calculus, we obtain that v satisfies (64)-1A(AΦp(v))=(p-1-γp-1)p-1q(x)v(α-γ)(p-1)/(p-1-γ),in(0,),AΦp(v)(0)=0,limxv(x)=0. Using Theorem 4, we deduce that problem (64) has a unique solution v such that (65)v(x)θ~β(x):={(x+1(L(s))1/(p-1)sds)(p-1-γ)/(p-1-α),if  β=p,1(1+x)(β-p)(p-1-γ)/((p-1)(p-1-α))×(L(1+x))(p-1-γ)/((p-1)(p-1-α)),if  p<β<(λ+1)(p-1-α)+(α-γ)pp-1-γ,1(1+x)(λ-p+1)/(p-1),if  β>(λ+1)(p-1-α)+(α-γ)pp-1-γ,1(1+x)(λ-p+1)/(p-1)×(1x+2L(s)sds)(p-1-γ)/((p-1)(p-1-α)),if  β=(λ+1)(p-1-α)+(α-γ)pp-1-γ. Consequently, we deduce that (63) has a unique solution u satisfying (66)u(x){(1+x(L(s))1/(p-1)sds)(p-1)/(p-1-α),if  β=p,(1+x)(p-β)/(p-1-α)(L(1+x))1/(p-1-α),if  p<β<(λ+1)(p-1-α)+(α-γ)pp-1-γ,(1+x)(p-1-λ)/(p-1-γ),if  β>(λ+1)(p-1-α)+(α-γ)pp-1-γ,(1+x)(p-1-λ)/(p-1-γ)(1-xηL(s)sds)1/(p-1-α),if  β=(λ+1)(p-1-α)+(α-γ)pp-1-γ.

Acciaio B. Pucci P. Existence of radial solutions for quasilinear elliptic equations with singular nonlinearities Advanced Nonlinear Studies 2003 3 4 511 539 MR2017245 ZBL1080.35019 Agarwal R. P. H. O'Regan D. Existence theorems for the one-dimensional singular p-Laplacian equation with sign changing nonlinearities Applied Mathematics and Computation 2003 143 1 15 38 10.1016/S0096-3003(02)00342-9 MR1979484 Agarwal R. P. H. O'Regan D. An upper and lower solution method for the one-dimensional singular p-Laplacian Georgian Academy of Sciences A 2003 28 13 31 MR1986715 Agarwal R. P. H. O'Regan D. Eigenvalues and the one-dimensional p-Laplacian Journal of Mathematical Analysis and Applications 2002 266 2 383 400 10.1006/jmaa.2001.7742 MR1880513 Bachar I. Ben Othman S. Mâagli H. Existence results of positive solutions for the radial p-Laplacian Nonlinear Studies 2008 15 2 177 189 MR2423292 Bachar I. Ben Othman S. Mâagli H. Radial solutions for the p-Laplacian equation Nonlinear Analysis: Theory, Methods & Applications 2009 70 6 2198 2205 10.1016/j.na.2008.02.119 MR2498307 Calzolari E. Filippucci R. Pucci P. Existence of radial solutions for the p-Laplacian elliptic equations with weights American Institute of Mathematical Sciences Journal 2006 15 2 447 479 10.3934/dcds.2006.15.447 MR2199439 Covei D.-P. Existence and asymptotic behavior of positive solution to a quasilinear elliptic problem in N Nonlinear Analysis: Theory, Methods & Applications 2008 69 8 2615 2622 10.1016/j.na.2007.08.039 MR2446357 ZBL1157.35366 Ghergu M. Rădulescu V. D. Nonlinear PDEs Mathematical Models in Biology, Chemistry and Population Genetics 2012 Heidelberg, Germany Springer Springer Monographs in Mathematics 10.1007/978-3-642-22664-9 MR2865669 Goncalves J. V. Santos C. A. P. Positive solutions for a class of quasilinear singular equations Electronic Journal of Differential Equations 2004 2004 56 1 15 MR2047412 ZBL1109.35309 Hai D. D. Shivaji R. Existence and uniqueness for a class of quasilinear elliptic boundary value problems Journal of Differential Equations 2003 193 2 500 510 10.1016/S0022-0396(03)00028-7 MR1998966 ZBL1042.34045 He X. Ge W. Twin positive solutions for the one-dimensional p-Laplacian boundary value problems Nonlinear Analysis: Theory, Methods & Applications 2004 56 7 975 984 10.1016/j.na.2003.07.022 MR2038732 Karls M. Mohammed A. Integrability of blow-up solutions to some non-linear differential equations Electronic Journal of Differential Equations 2004 2004 1 8 MR2046988 ZBL1050.34045 Kim C.-G. Lee Y.-H. Existence of multiple positive radial solutions for p-Laplacian problems with an L1-indefinite weight Taiwanese Journal of Mathematics 2011 15 2 723 736 MR2810178 Pucci P. García-Huidobro M. Manásevich R. Serrin J. Qualitative properties of ground states for singular elliptic equations with weights Annali di Matematica Pura ed Applicata IV 2006 185 S205 S243 10.1007/s10231-004-0143-3 MR2187761 ZBL1115.35050 Brezis H. Kamin S. Sublinear elliptic equations in n Manuscripta Mathematica 1992 74 1 87 106 10.1007/BF02567660 MR1141779 ZBL0761.35027 Chemmam R. Dhifli A. Mâagli H. Asymptotic behavior of ground state solutions for sublinear and singular nonlinear Dirichlet problems Electronic Journal of Differential Equations 2011 2011 88 1 12 MR2821533 ZBL1225.31002 Edelson A. L. Entire solutions of singular elliptic equations Journal of Mathematical Analysis and Applications 1989 139 2 523 532 10.1016/0022-247X(89)90126-1 MR996976 ZBL0679.35003 Ghergu M. Rădulescu V. Ground state solutions for the singular Lane-Emden-Fowler equation with sublinear convection term Journal of Mathematical Analysis and Applications 2007 333 1 265 273 10.1016/j.jmaa.2006.09.074 MR2323490 ZBL1211.35128 Lair A. V. Shaker A. W. Classical and weak solutions of a singular semilinear elliptic problem Journal of Mathematical Analysis and Applications 1997 211 2 371 385 10.1006/jmaa.1997.5470 MR1458503 ZBL0880.35043 Mohammed A. Ground state solutions for singular semi-linear elliptic equations Nonlinear Analysis: Theory, Methods & Applications 2009 71 3-4 1276 1280 10.1016/j.na.2008.11.080 MR2527547 ZBL1167.35371 Santos C. A. On ground state solutions for singular and semi-linear problems including super-linear terms at infinity Nonlinear Analysis: Theory, Methods & Applications 2009 71 12 6038 6043 10.1016/j.na.2009.05.050 MR2566507 ZBL1178.35169 Seneta E. Regularly Varying Functions 1976 508 Berlin, Germany Springer Lecture Notes in Mathematics MR0453936 Trubek J. Asymptotic behavior of solutions to Δu+Kuσ=0 on n for n3 Proceedings of the American Mathematical Society 1989 106 4 953 959 10.2307/2047279 MR987615 ZBL0705.35012